Intravenous immunoglobulin efficacy on pembrolizumab induced severe toxic epidermal necrolysis. Issue 1 (January 2022) - Kian, Waleed; Zemel, Melanie; Elobra, Firas; Sharb, Adam A.; Levitas, Dina; Assabag, Yarden; Alguayn, Farouq; Yakobson, Alexander; Rouvinov, Keren; Fuchs, Lior
Abstract : Pembrolizumab is an immune checkpoint inhibitor used in many different cancers. Several immune-related adverse events (irAEs) have been associated with pembrolizumab, including toxic epidermal necrolysis. Here, we are presenting a patient with non-small cell lung cancer that developed toxic epidermal necrolysis 3-days following initiation of pembrolizumab. Following high-dose steroid therapy, intravenous immunoglobulin 2 g/kg was initiated and resulted in complete resolution of all his irAEs. To our knowledge, this is the first reported case of total re-epithelialization and resolution of immune checkpoint inhibitor-induced toxic epidermal necrolysis following the use of intravenous immunoglobulin.